Comparative Estimation of Stability of Gold Nanoparticles in Aqueous Solution by Spectrophotometric Absorbance and Zeta Potential Methods - Silvia , Maquina Alo (IRC, 2016)
In this work nanoparticles (NP) are synthesized by reducing tetrachloroaurate (HAuCl4) aqueous solution with palm oil leaves extract in the presence of water and 1-Ethyl-3- methylimidazolium acetate (emim acetate) as solvents. The objective of this work is to study the stability of the gold nanoparticle solution (AuNP) by measuring UVspectrophotometric absorbance, zeta potential and particle size distribution. The methods used allow the assessment of stability of the colloidal solution. During the experiment; the volume of leaf extract, was changed to estimate particle size distribution, zeta potential and the change in the absorbance